A case report of a patient with wide complex tachycardia due to Wolff–Parkinson–White syndrome mimicking ventricular tachycardia. Issue 9 (15th September 2021) - Preisendörfer, Stefan; Hessling, Gabriele; Deisenhofer, Isabel; Bourier, Felix
Abstract: Background: Wide complex tachycardia (WCT) associated with syncope as manifestation of an underlying, life-threatening arrhythmia might potentially be the harbinger of sudden cardiac death. Identifying the aetiology of a WCT is imperative to provide appropriate treatment and prevent recurrence. Case summary: We report the case of a 22-year-old male who had been experiencing haemodynamically significant WCT leading to syncope at the age of 13 years. As the patient and the family rejected an electrophysiological (EP) study, he had received an implantable cardioverter-defibrillator (ICD) for secondary prevention. After 7 years of experiencing multiple shocks, the patient finally gave consent to an EP study, which identified a left-sided accessory atrioventricular pathway that was successfully ablated during the same procedure. Discussion: The differential diagnosis of WCT might be challenging and includes both ventricular and supraventricular tachycardias. In young patients without structural heart disease experiencing WCT, an EP study should be offered before ICD implantation to make a final diagnosis with the potential to provide definitive treatment.